Fabrication and Optical-Electrical Characterization of Al/p-Si/CdO/Au Photodiode - Cavas, Mehmet (Springer International Publishing Ag, 2018)
In this study, CdO thin film was fabricated using sol-gel spin coating method and it was grown onto p-type silicon. After this process is completed morphological properties of the CdO thin film were studied using atomic force microscopy. Also, the optical properties of the CdO thin film were studied. The transmittance of the thin film showed about 85% transparent and the band gap was found to be 3.47 eV. Also, the current-voltage (I-V) of the photodiode was measured under dark and at the different intensity of illumination. Besides, the capacitance-voltage (C-V) of photodiode was measured at a different frequency.
12th International Conference on Mechatronics -- SEP 06-08, 2017 -- Brno, CZECH REPUBLIC
Keywords: Nanomaterials; Optical sensor; Photodiode; Thin film